Institutional enrollment volume and clinical outcomes after surgery or chemoradiotherapy for clinical stage I esophageal squamous cell carcinoma: a supplementary analysis of JCOG0502 - Kazuhiro Shiraishi; Ken Kato; Yuya Ishikawa; Keita Sasaki; Hiroyuki Daiko; Yoshinori Ito; Takeshi Kajiwara; Takashi Kojima; Hiroshi Miyata; Masaki Ueno; Satoru Nakagawa; Shinsuke Sato; et al. (Esophagus, 2026)
Abstract Background Surgery and chemoradiotherapy (CRT) are standard options for clinical stage I esophageal squamous cell carcinoma (ESCC). JCOG0502, a multicenter, non-randomized, parallel-group comparison, demonstrated the non-inferiority of definitive CRT compared with surgery for overall survival (OS) in patients with cT1bN0M0 ESCC; however, institutional differences may influence outcomes. This study explored inter-institutional heterogeneity in survival and adverse events (AEs) among patients in JCOG0502. Methods Among 379 enrolled patients, 364 were analyzed. Institutions enrolling ≥ 13 patients, corresponding to the median institutional trial enrollment, were classified as high-enrollment institutions (High), whereas those enrolling < 13 patients were classified as low-enrollment institutions (Low). Institutional trial enrollment was evaluated as an exploratory indicator, rather than as a direct measure of institutional case or procedural volume. The primary endpoint was OS. Secondary endpoints were progression-free survival (PFS) and AEs. Results In the surgery group, institutional trial enrollment volume was not significantly associated with OS (HR for High vs. Low, 0.73; 95% CI, 0.40–1.35). Similarly, no significant association was observed in the CRT group (HR, 1.12; 95% CI, 0.59–2.13). Findings for PFS were consistent with these OS results in both groups. Myocardial ischemia or infarction occurred in 5 patients in Low and none in High in the CRT group. Conclusions No clear association was identified between institutional trial enrollment volume and survival outcomes in either the surgery or CRT group. However, clinically meaningful differences could not be excluded. The observed differences in selected toxicities, including myocardial ischemia, should be considered hypothesis-generating.